Utilizing Flashcards to Enhance Students’ Writing Skill of Descriptive Text in SMA Negeri 2 Semarang (psnppg, 2023)
This study aims to improve the writing skills of grade X-6 students of SMA N 2 Semarang as a result of English learning achievements using flashcards media on describing people material. This study is a classroom action research. The research is conducted in two cycles and each cycle consists of planning, execution, observation, and reflection. Data collection techniques in this study are written tests and observations. The results of this study showed that in the first cycle 91.7% of students had reached the Minimum Completeness Criteria (KKM) with an average score of 82.2. In the second cycle, 100% of students have reached the Minimum Completeness Criteria (KKM) with an average score of 87.8. Based on these results, it can be concluded that the application of media flashcards in English learning can improve the writing skills of grade X-6 students of SMA N 2 Semarang.
Keywords: English Learning Outcomes; Flashcards; Vocabulary; Writing Skill; Descriptive Text